HUBUNGAN KARAKTERISTIK LANSKAP DENGAN PREFERENSI SITUS OVIPOSISI KUPU-KUPU DI RUANG TERBUKA HIJAU KAWASAN JAKARTA TIMUR - DIANA, PUTRI; DJAMAHAR, REFIRMAN; ISFAENI, HANUM (LPPM Universitas Negeri Jakarta, 2015)
ABSTRACT Urban area is dominated by land that functioned of the interest of economy and settlement, but only a few land allocated for wildlife. The butterflies was one of the wildlife that could be found in urban areas.The remaining habitat that can be used by butterflies assumed confined to the urban green space. Based on its life cycle, the butterflies having an initial phase (egg to larvae) is a phase which is generally require specific habitat. This research aims to determine the relationship between landscape characteristic and oviposition site preferences of butterfly. This research was conducted on April to June, 2014 at fifteen urban green spaces in East Jakarta by using descriptive survey technique. Landscape characteristics measured include area, perimeter, lawn area, closed vegetation area, open vegetation area, non vegetation area. Landscape characteristic not only measured from urban green space, but also measured from the area around urban green space within the scope of 100 meters buffer. Results show that there is a relationship between landscape characteristic and oviposition site preferences. Significant positive correlation between the abundance and area correlation coefficients rs (0,546), open vegetation area rs (0,758) and non vegetation buffer area rs (0,688). There was no significant correlation between the abundance with perimeter area, lawn area, closed vegetation area, non vegetation area, lawn buffer, open vegetation buffer and closed vegetation buffer. Keywords: caterpillar,landscape characteristic, oviposition site, preferences, urban green space